Microorganismos asociados a la enfermedad de marchitez bacteriana en Dendrocalamus asper (Schult. & Schult. f.) Backer ex K. Heyne (bambú gigante) en el grupo de fuerzas especiales N° 26 Cenepa del cantón Quevedo - Vera Carranza, Marlon Gabriel (2022)
The objective of this research was to determine which are the microorganisms associated with the bacterial wilt disease in D. asper (giant bamboo). The material was collected from diseased shoots in a giant bamboo forest located on the premises of the Special Forces Group No. 26 CENEPA and analyzed in the microbiology laboratory of the Quevedo State Technical University. Two previously modified culture media Potato Dextrose Agar (Streptomycin, 1mg/L) and Nutritive Agar (Affiliated, 1mg/L) were used.